After Total Knee Arthroplasty, Monitored Active Ankle Pumping Improves Lower Leg Circulation More Than Unmonitored Pumping: A Pilot Study - Ming-Chou Ku; Yuan-Hsin Tsai; Po-Cheng Cheng; Ting-I Yang; Hui-Wen Ho; Min-Fei Liao; Yu-Tzu Tseng; Ming-Tsung Lee; Yen-Nien Chen (Applied Sciences, 2022)
(1) Background: deep venous thrombosis (DVT) has long been recognized as the most devastating complication after total knee replacement (TKR). To prevent DVT, intermittent pneumatic compression to improve venous return in the lower leg has been advocated by surgeons. Physical activities such as active ankle pumping and early mobilization have been recommended as auxiliary measures to increase venous return in the lower leg and help in ambulation after TKR. In this study, in order to remind patients to exercise their ankle actively and efficiently after TKR, a foot band with motion sensor and reminder alarm was used. (2) Methods: The patients were randomly allocated into three groups according to the therapeutic protocols. The patients in group 1 conducted active ankle pumping without any reminders, those in group 2 underwent intermittent pneumatic compression, and those in group 3 conducted active ankle pumping with ankle motion sensor/reminder. The parameters of blood flow, namely, peak flow velocity and flow volume, in the bilateral common femoral vein and popliteal vein on the 1st, 3rd, and 14th days after surgery were measured using the echo technique, an index to evaluate the effect on promotion of venous return, among the three groups. (3) Results: The peak flow velocity and flow volume of the operative limb in group 3 (with motion sensor/reminder) were significantly higher than those in other groups. The peak flow velocity and flow volume in the popliteal vein in group 3 increased by 112% and 93.8%, respectively, compared to group 1 on the 14th day. No significant difference in peak flow velocity or flow volume was found in the nonoperative limb between the groups. (4) Conclusions: According to the results, a motion sensor/reminder with vibration alarms can improve the performance of active ankle pumping exercises in improving lower leg circulation, and hence may reduce the risk of DVT.